Changes in physical activity by context and residential greenness among recent retirees: Longitudinal GPS and accelerometer study - Pasanen S; Halonen JI; Gonzales-Inca C; Pentti J; Vahtera J; Kestens Y; Thierry B; Brondeel R; Leskinen T; Stenholm S (ELSEVIER SCI LTD, 2025)
This study examined the changes in accelerometer-measured physical activity by GPS-measured contexts among Finnish retirees (n = 45 (537 measurement days)) participating in a physical activity intervention. We also assessed whether residential greenness, measured with Normalized Difference Vegetation Index, moderated the changes. Moderate-to-vigorous physical activity (MVPA) increased at home by 7 min/day, (P < 0.001) and during active travel by 5 min/day (P = 0.03). The participants with the highest vs. lowest greenness had 25 min/ day greater increase in MVPA over the follow-up (P for Time*Greenness interaction = 0.04). In conclusion, retirees participating in the intervention increased their MVPA both at home and in active travel, and more so if they lived in a greener area.